HIF-1 reduces ischaemia-reperfusion injury in the heart by targeting the mitochondrial permeability transition pore. - Ong, S; Lee, W; Theodorou, L; Kodo, K; Lim, S; Shukla, D; Briston, T; Kiriakidis, S; Ashcroft, M; Davidson, S; Maxwell, P; Yellon, D; et al. (Oxford University Press, 2014)
AIMS: Hypoxia-inducible factor-1 (HIF-1) has been reported to promote tolerance against acute myocardial ischaemia-reperfusion injury (IRI). However, the mechanism through which HIF-1 stabilization actually confers this cardioprotection is not clear. We investigated whether HIF-1α stabilization protects the heart against acute IRI by preventing the opening of the mitochondrial permeability transition pore (MPTP) and the potential mechanisms involved. METHODS AND RESULTS: Stabilization of myocardial HIF-1 was achieved by pharmacological inhibition of prolyl hydroxylase (PHD) domain-containing enzyme using GSK360A or using cardiac-specific ablation of von Hippel-Lindau protein (VHL(fl/fl)) in mice. Treatment of HL-1 cardiac cells with GSK360A stabilized HIF-1, increased the expression of HIF-1 target genes pyruvate dehydrogenase kinase-1 (PDK1) and hexokinase II (HKII), and reprogrammed cell metabolism to aerobic glycolysis, thereby resulting in the production of less mitochondrial oxidative stress during IRI, and less MPTP opening, effects which were shown to be dependent on HKII. These findings were further confirmed when HIF-1 stabilization in the rat and murine heart resulted in smaller myocardial infarct sizes (both in vivo and ex vivo), decreased mitochondrial oxidative stress, and inhibited MPTP opening following IRI, effects which were also found to be dependent on HKII. CONCLUSIONS: We have demonstrated that acute HIF-1α stabilization using either a pharmacological or genetic approach protected the heart against acute IRI by promoting aerobic glycolysis, decreasing mitochondrial oxidative stress, activating HKII, and inhibiting MPTP opening.